PERALIHAN HAK KEPEMILIKAN HARTA KEKAYAAN YANG TIDAK DIKETAHUI PEMILIK DAN AHLI WARISNYA DI BALAI HARTA PENINGGALAN KOTA MEDAN - Marta Afdel Bonita Sihombing; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Switch means the transfer of ownership of the land from its owner to other parties due to the existence of a legal act. Transfer of rights of ownership of assets that are not known to exist based on Article 463 of the Civil Code which states that the Heritage Center as a representative for the people who are not known to exist to take care of property that is not present based on the stipulation of the District Court. In the submission, Heritage Hall Medan is not fully perform its obligations due to some constraints. Heritage Hall is the unit law enforcement in the field of wealth and trust in the Ministry of Justice. Heritage Hall authorities, obliged and responsible in dealing with problems in the field of guardianship, wardship, ketidakhadiranan, inheritance derelict and bankruptcy. Absence (afweigheid) is intended to provide certainty of one's civil rights to both the left and abandoned.This type of research can be classified in this type of sociological research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Center for Heritage city of Medan, while the sample population is a whole party with regard to the problems examined, the data source used, primary data, virgin secondary data and tertiary data collection techniques in this study with interviews and literature study.From the results of research and discussion can be concluded that, First, transition ownership of assets of unknown owners and their heirs are not going transition between the owner and occupants because of the obstacles that make Heritage Hall did not carry out its obligations in its staff, in the rules. Secondly, the legal consequences of the transfer of rights ownership of the assets of unknown owners and their heirs that no transfer of ownership of the assets to the occupant and the occupant can only occupy the building as an educational building.Keywords: Transition - Circumstances Not Present (afwezigheid) - Heritage Hall